Profiling the Bioactive Richness (Flavonoids, Phenolic Acids and Vitamins) of Acacia Leaves - Raju, Sagi; Nagalakshmi, Devanaboyina; Kumari, Nagireddy Nalini; Sravanthi, Boini; Vijay, Kolli (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Phytochemicals derived from plants have gained considerable attention for their health-promoting properties, including antioxidant, anti inflammatory, and disease-preventing capabilities. This study focuses on the phytochemical profiling of Acacia leaf extracts, highlighting  their potential as nutraceutical and animal health supplements. Using LC-MS/MS, we identified and quantified key flavonoids, phenolic  acids, and vitamins present in Acacia leaves. Significant levels of bioactive flavonoids such as quercetin, rutin, hesperetin, naringenin,  and luteolin were detected, with quercetin-3-rutinoside (rutin) showing the highest concentration. Phenolic profiling revealed abundant  levels of gallic acid, p-coumaric acid, and dihydroxybenzoic acid, compounds known for their antioxidant and antimicrobial properties.  In addition to phytochemicals, Acacia leaves were found to be rich in essential vitamins, particularly water-soluble B-complex vitamins  (thiamine, niacin, pantothenic acid) and fat-soluble vitamins E and K1. These findings demonstrate the multifunctional value of Acacia  leaf extracts in promoting health and productivity in both humans and animals. The results support further exploration of Acacia as a  sustainable source of natural antioxidants and micronutrients for functional food, pharmaceutical, and animal feed applications.
Keywords: Acacia leaf extract, Flavonoids, LC-MS/MS profiling, Phenolic acids, Phytochemicals